2022
DOI: 10.1097/prs.0000000000008969
|View full text |Cite
|
Sign up to set email alerts
|

Facial Gender Confirmation Surgery: The Lower Jaw. Description of Surgical Techniques and Presentation of Results

Abstract: Background: Of the primary procedures associated with facial gender confirmation surgery, those involving the mentomandibular complex have received the least attention in the literature. Methods: The authors present their experience with 837 trans feminine patients operated on for facial gender confirmation surgery who underwent mandibular bone contouring procedures, including bone contouring, chin and mandibular body and angle ostectomies, and osteotomies to reposition the chin. The authors describe the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
(68 reference statements)
0
11
0
Order By: Relevance
“…In recent years, facial GAS (FGAS) has received increased attention, and current literature supports its benefits. Eight recent publications include 1 prospective cohort (Morrison et al., 2020 ), 5 retrospective cohort (Bellinga et al., 2017 ; Capitán et al., 2014 ; Noureai et al., 2007 ; Raffaini et al., 2016 ; Simon et al., 2022 ), and 2 cross-sectional studies (Ainsworth & Spiegel, 2010 ; van de Grift, Elaut et al., 2018 ). All 8 studies clearly demonstrated individuals were very satisfied with their surgical results (between 72% and 100% of individuals).…”
Section: Chapter 13 Surgery and Postoperative Carementioning
confidence: 99%
“…In recent years, facial GAS (FGAS) has received increased attention, and current literature supports its benefits. Eight recent publications include 1 prospective cohort (Morrison et al., 2020 ), 5 retrospective cohort (Bellinga et al., 2017 ; Capitán et al., 2014 ; Noureai et al., 2007 ; Raffaini et al., 2016 ; Simon et al., 2022 ), and 2 cross-sectional studies (Ainsworth & Spiegel, 2010 ; van de Grift, Elaut et al., 2018 ). All 8 studies clearly demonstrated individuals were very satisfied with their surgical results (between 72% and 100% of individuals).…”
Section: Chapter 13 Surgery and Postoperative Carementioning
confidence: 99%
“…Jawline-contouring techniques include osteotomies and ostectomies at the level of the mandibular lower border, as well as bone sculpture that involves burring the surface. 5 Access to any area on the jaw must be intraoral. Likewise, we recommend the use of ultrasonic technology and a lower-border–supported cutting guide for every ostectomy and osteotomy performed.…”
Section: Lower Jaw Surgerymentioning
confidence: 99%
“…In cases where a more extended ostectomy of the lower jaw border is needed, the use of a triple approach with basal tunneling below the mental nerves is recommended to protect them with an island of mucosa. 5 In contrast, an excessively extensive incision (mandibular degloving) exposes the nerves and risks their integrity.…”
Section: Complications Related To the Surgical Approach Nerve Damagementioning
confidence: 99%
See 2 more Smart Citations